How Interface Design Nudges Instagram Users Toward Posting Less Permanent Content - Driya, Putu Dhanu; Sumerta, Ni Putu Abigail Firsta; Diputra, I Gusti Nyoman Anton Surya (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2026)
This study examines the effect of Instagram interface design nudges on Gen Z users’ preference for ephemeral content over permanent feed posts, and the mediating roles of cognitive biases and self-presentation concerns. A survey of 347 Gen Z users was analyzed using parallel mediation (PROCESS Model 4). Results indicated that interface nudges significantly predicted cognitive biases (b = 0.903, p = 0.047) and self-presentation concerns (b = 0.807, p = 0.039), but neither mediator significantly influenced ephemeral posting (indirect effect M1 = 0.0021, 95% CI [-0.0244, 0.0192]; M2 = 0.0003, 95% CI [-0.0165, 0.0236]). The direct effect of nudges on ephemeral posting was significant (b = 0.060, p = 0.031), indicating that UI design directly encourages temporary content sharing. These findings highlight the dominant role of interface design in guiding user behavior, suggesting that nudges influence ephemeral posting primarily through direct behavioral effects rather than mediated psychological mechanisms.